Pemberian Beberapa Konsentrasi dan Interval Penyemprotan Ekstrak Daun Sirsak terhadap Hama Myzus persicae Sulzer pada Tanaman Cabai - Yunel Venita; Hafiz Fauzana; Mukti ' (Universitas Riau, 2009)
The usage of synthetic insecticide commonly used to control pest has negative impact on human helath and environment. The soursop (Annona muricata L.) leaves had been frequently tested for controlling pest at various concentration and spraying interval. This research was conducted at farmer field at Simpang baru panam, Pekanbaru city. This research was carried out by factorial experiment of group randomized design with two factors, four and two levels, and three repklications. The first factor was different concentration of soursop leaves extract, and the second factor was the spraying interval was effective to prevent Myzus persicae pest.